Service Supply Chain Risk Analysis and Control of Port Based on the using HOR Approach - Perdana, Kevin Gabrianto Rizky; Partiwi, Sri Gunani (Jurnal Teknologi dan Manajemen, 2026)
Ports have an important role in the maritime transportation system but also face various obstacles and threats to different types of risks. Economic conditions and activities that tend to be complex and uncertain such as the threat of the COVID-19 pandemic, climate change, and geopolitics cause port development and operations to face various challenges and uncertainties.  The ASDP port of the Juata Tarakan ferry has become one of the important parts of community activities to travel from Tarakan island to the surrounding islands such as Tana Tidung and Nunukan. Various studies have been conducted to learn about the operational phases of ports, but not about the overall life cycle. In addition to operational factors, there are environmental factors that still need to be explored in order to avoid failure to distinguish the causes and consequences of risks from risk events. In this study, the process of identification, analysis, and risk mitigation is carried out using a house of risk approach to be able to identify risk events and risk causative agents. This study seeks to explore the risk that is a key component by looking for the relationship between one risk agent and another risk agent and its impact on port companies. Risk prevention actions are discussed in this study in order to be an insight to rethink port risks and design strategic management. The purpose of this study is to help port authorities, especially ASDP ferry, to develop an understanding and management approach to risk from all aspects of the life cycle of the port